Fretting fatigue of 6201 aluminum alloy wires of overhead conductors. (December 2020) - Matos, I.M.; Rocha, P.H.C.; Kalombo, R.B.; Veloso, L.A.C.M.; Araújo, J.A.; Castro, F.C.
Highlights: New experimental data for AA6201-T81 wires under fretting fatigue. Nonlocal life estimation approach for wires of overhead conductors. Effective procedure to obtain the size of the fatigue process zone. Elastic-plastic contact model significantly improved estimated lives. Abstract: Fretting fatigue tests were conducted on 6201-T81 aluminum alloy wires of an AAAC 900 MCM conductor. A finite element-based contact model combined with a nonlocal Smith–Watson–Topper criterion was used to estimate fatigue life. To account for the stress gradients beneath the contact, an average stress over a fatigue damage zone was adopted. A procedure for determining the size of the damage zone from V-notched wire test data is presented. Fatigue lives estimated using stresses from a linear elastic contact model were overly conservative, while the use of an elastic-plastic contact model significantly improved the estimates.